Compare mDCs and pDCs between two distinct patients groups in acute HIV-1 infection - Jiao, Yanmei (BioMed Central, 2014)
The role of DCs in primary HIV-1 infection remains uncertain. In this study, we enrolled two different groups of subjects with acute HIV-1 infection. One group progressed to CD4 counts below 200 cells/μl within 2 years of HIV-1 infection (CD4 Low Group), while the other group maintained CD4 counts above 500 cells/μl (CD4 High Group). We did not find statistical difference in the pDC number between the two groups during acute HIV-1 infection. However, the mDC number was significantly lower in the CD4 Low Group than in the CD4 High Group.